2021
DOI: 10.1177/08862605211055154
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypes About Battered Women and Victim’s Self-Defense: Legal Implications

Abstract: Recent research on the practices of justice operators with women victims of intimate partner violence has evidenced the existence of gender stereotypes and gender-blind practices in the Spanish legal system (Albertín et al., 2020; García Jiménez et al., 2019, 2020), as well as the graves consequences that such practices imply for these women. In this context, the present study explored the existence of a battered woman stereotype and its variation when the victim defends herself from the abuser. An opportunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…This included two Queensland cases where psychiatrists testified under an expansive BWS framework . Although presenting evidence under BWS, the psychiatrists took an expansive approach that did not pathologize the defendant, but instead described the limited solutions available to women in leaving a violent relationship ( R v. Falls , 2010), or explicitly explained that the concept of BWS is not a psychiatric diagnosis ( R v. Irsliger , 2012) (see Douglas, 2012 ; Sheehy et al, 2014 ). In two cases, experts testified under the framework of social context evidence.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This included two Queensland cases where psychiatrists testified under an expansive BWS framework . Although presenting evidence under BWS, the psychiatrists took an expansive approach that did not pathologize the defendant, but instead described the limited solutions available to women in leaving a violent relationship ( R v. Falls , 2010), or explicitly explained that the concept of BWS is not a psychiatric diagnosis ( R v. Irsliger , 2012) (see Douglas, 2012 ; Sheehy et al, 2014 ). In two cases, experts testified under the framework of social context evidence.…”
Section: Resultsmentioning
confidence: 99%
“…Drawing upon the various sources of data, this study examined and coded each case for their (a) legal outcomes , including the original charge laid, the method of resolution (i.e., guilty plea or trial), the conviction received (if any), the basis of the conviction, and the sentenced received. The study also coded (b) defendant characteristics previously found to impact on the legal treatment of abused women ( Douglas, 2012 ), such as their Indigenous status, whether they have a previous criminal history, and whether they had previously fought back. Lastly, the study also recorded (c) case characteristics likely to influence legal outcomes, including whether the case involved expert testimony or evidence, the immediate circumstances of the offence, the presence of alcohol or illicit drug use at the time of offence, and the method in which the defendant killed her abusive partner.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At a broad level of analysis, this has the potential to influence policy and practice, particularly for first responders such as police. This protoscript also adds to the crime script literature by highlighting the methods used by victims to protect themselves or others during incidents and goes a little way in challenging stereotypes ( Delgado-Alvarez & Sanchez-Prada, 2021 ) including around victim agency and their ability to effectively manage their safety ( Nancarrow et al, 2020 ; Tolmie et al, 2018 ). This study includes additional information relevant to situational crime prevention by articulating the different methods used by offenders and victims, and the different intervention methods used.…”
Section: Discussionmentioning
confidence: 99%